Implementation of Modern and Traditional Market Structuring Policies in The Perspective of Business Competition - Rahman, Alip Rahman; Nabilla, Anandya Salsa (Green Publisher Indonesia, 2023)
The implementation of the Modern Market Control Policy in the City of Cirebon is the responsibility of the Regional Government of the City of Cirebon in order to control the development of the modern market and protect the traditional market against the continuity of business competition in the City of Cirebon in line with the spread of the establishment of modern markets spread across the City of Cirebon. The formulation of the problem in this research are (1) Local Government Policy in structuring and controlling modern shops; (2) the constraints of the Cirebon City government in implementing and controlling the existence of modern shops. This research uses normative legal research, namely the approach of field research by seeing and observing what is happening in the field and the application of legislation in its implementation. The object of this research is the Department of Trade and Investment of the City of Cirebon. The results of this study are: The implementation of Cirebon City Government policies in the context of controlling Modern Markets in Cirebon City, namely by implementing a Licensing Moratorium to maintain order with the growth of modern markets in Cirebon City, this also needs to be done in the context of business protection for MSMEs. Obstacles faced by the Cirebon City Government include obstacles in supervising and controlling unlicensed modern shops/markets.